2022
DOI: 10.3389/fpubh.2022.968837
|View full text |Cite
|
Sign up to set email alerts
|

When workaholism is negatively associated with burnout: A moderated mediation

Abstract: AimPrevious theory and research postulate that workaholism is one of the important factors that contribute to burnout. The present study aimed to analyze the role of psychological capital as a mediator between the two. Moreover, the study examined the moderating role in the stated mediated relationship.MethodsThe researchers approached a sample of university teachers (N = 1,008) including both male (n = 531) and female (n = 477) university teachers by using a multi-stage random sampling technique. For this pur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 58 publications
0
5
0
1
Order By: Relevance
“…Furthermore, higher work expectations necessitate greater mental effort, which stresses out employees and makes them feel burned out, which in turn leads to absenteeism. Burnout symptoms such as emotional depletion are brought on by workplace stress, and counterproductive work conduct is a behavioural response to job-related stress (Fatima Makhdoom et al, 2019). Leiter et al, (2003) found that depersonalisation and emotional weariness were more strongly connected with work-related stress and resources than they were with personal achievement.…”
Section: The Mediating Effect Of Strain Between Job Demand and Cwbmentioning
confidence: 99%
“…Furthermore, higher work expectations necessitate greater mental effort, which stresses out employees and makes them feel burned out, which in turn leads to absenteeism. Burnout symptoms such as emotional depletion are brought on by workplace stress, and counterproductive work conduct is a behavioural response to job-related stress (Fatima Makhdoom et al, 2019). Leiter et al, (2003) found that depersonalisation and emotional weariness were more strongly connected with work-related stress and resources than they were with personal achievement.…”
Section: The Mediating Effect Of Strain Between Job Demand and Cwbmentioning
confidence: 99%
“…Following the COR theory, which suggests that people employ valued resources to respond to stress and to build a reservoir for future needs, the stress literature has identified PsyCap as a mediator between stressful contexts and burnout. PsyCap has been found to be a mediator between occupational stress and burnout ( 40 ), between workaholism and burnout ( 41 ), and between workplace bullying and burnout ( 42 ). Following theoretical and empirical literature, we hypothesized that insufficient sleep would positively influence burnout through PsyCap.…”
Section: Theoretical Background and Hypothesesmentioning
confidence: 99%
“…Hal ini dapat dilakukan dengan memastikan bahwa tempat kerja merupakan sumber kepuasan untuk kebutuhan psikologis dasar internal, misalnya otonomi, kompetensi, keterkaitan. (Makhdoom et al, 2022) menghabiskan lebih banyak waktu di tempat kerja dapat menghasilkan lebih banyak pekerjaan. Karnanya, itu berhubungan positif dengan eustress yang membantu karyawan mengambil tugas pekerjaan sebagai tantangan, sehingga mereka bisa merasa dewasa.oleh karena itu, seperti disebutkan sebelumnya, kecanduan kerja memprediksi secara positif dan empat subskalanya, termasuk harapan, ketahanan, kemanjuran diri, dan optimisme.…”
Section: Hasil Dan Pembahasanunclassified